MicroRNA-focused CRISPR-Cas9 library screen reveals fitness-associated miRNAs - Kurata, Jessica S.; Lin, Ren-Jang (RNA (Cambridge), 2018)
MicroRNAs (miRNAs) are post-transcriptional gene regulators that play important roles in the control of cell fitness, differentiation, and development. The CRISPR-Cas9 gene-editing system is composed of the Cas9 nuclease in complex with a single guide RNA (sgRNA) and directs DNA cleavage at a predetermined site. Several CRISPR-Cas9 libraries have been constructed for genome-scale knockout screens of protein function; however, few libraries have included miRNA genes. Here we constructed a miRNA-focused CRISPR-Cas9 library that targets 1594 (85%) annotated human miRNA stem–loops. The sgRNAs in our LX-miR library are designed to have high on-target and low off-target activity, and each miRNA is targeted by four to five sgRNAs. We used this sgRNA library to screen for miRNAs that affect cell fitness of HeLa or NCI-N87 cells by monitoring the change in frequency of each sgRNA over time. By considering the expression in the tested cells and the dysregulation of the miRNAs in cancer specimens, we identified five HeLa pro-fitness and cervical cancer up-regulated miRNAs (miR-31-5p, miR-92b-3p, miR-146b-5p, miR-151a-3p, and miR-194-5p). Similarly, we identified six NCI-N87 pro-fitness and gastric cancer up-regulated miRNAs (miR-95-3p, miR-181a-5p, miR-188-5p, miR-196b-5p, miR-584-5p, and miR-1304-3p), as well as three anti-fitness and down-regulated miRNAs (let-7a-3p, miR-100-5p, and miR-149-5p). Some of those miRNAs are known to be oncogenic or tumor-suppressive, but others are novel. Taken together, the LX-miR library is useful for genome-wide unbiased screening to identify miRNAs important for cellular fitness and likely to be useful for other functional screens.